Village’s Website Development Model As Information Media In Pesawaran District - Oktiani, Hestin; Gunawibawa, Eka Yuda; Effendy, M Yusuf (Universitas Islam Negeri Raden Intan Lampung, 2022)
Lampung Province adopts rural development with the smart village concept as a leading development program based on information and communication technology. In this concept the website has a strategic position in village development. Law Number 6 of 2014 concerning Villages and Government Regulation Number 34 of 2014 mandates village governments to provide the best possible public services and information to the community. Pesawaran District is an area where the village website is developing well. In 2018 there were 58 villages that had the desa.id domain and in 2020 there were 133 of the 148 villages. There are 30 villages that already have an active village website using the domain name desa.id. This is the result of implementing the village website development model carried out. The development model is the various efforts and policies as well as the synergy of various parties in managing the village website. Based on the results of interviews, observation and documentation search, it is known that the village website development model in Pesawaran District involves several parties, namely the Pesawaran Office of Communication and Information, village website operators, villagers and external parties. The Office of Kominfo Pesawaran as an external agent of change becomes the center of the relationship pattern in the model and is involved in the entire series of village website development processes, starting from the socialization process, licensing, management, monitoring and evaluation of village websites. There is an active role of ASN of the Ministry of Communication and Information which uses various media as a means of socialization and consultation. Other external agents have not been heavily involved. Internal agents of change, namely the village head, operators, and residents, greatly determine the sustainability of the website, but it is not optimal. There are still obstacles in developing village websites as part of smart village development.